An energy efficient authentication scheme for wireless body area networks based on the bilinear pairings. (2018) - Dai, Songsong; Jiang, Linmei; He, Shan; Guo, Donghui
With the popularity of wearable electronic devices, much attention has been paid to wireless body area networks (WBANs) for health monitoring. However, by the limited energy of electronic devices, WBANs not only need to consider the security and privacy preservation but also to consider the low power consumption implementation. Recently, Wang and Zhang presented an authentication scheme for WBANs. Unfortunately, in this paper, we will show their scheme is vulnerable to impersonation attack. Then we present a new authentication scheme for WBANs based on the bilinear pairings. Our scheme not only provides mutual authentication and client anonymity but also resists well-known cryptographical attacks. We also use the BAN logic to demonstrate the validity of our scheme. Compared with Wang-Zhang scheme, the energy consumption of our scheme is reduced by 1.79%.